2008
DOI: 10.1016/j.virusres.2008.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of siRNA mediated suppression of signaling lymphocyte activation molecule on replication of peste des petits ruminants virus in vitro

Abstract: Signaling lymphocyte activation molecule (SLAM) expression was inhibited in B95a cell line using siRNA and the effect of SLAM inhibition on peste des petits ruminants virus (PPRV) replication and infectivity titre was studied. SLAM suppression was assessed using real-time PCR and flow cytometry to confirm suppression at the m-RNA and protein levels, respectively. Three chemically synthesized siRNAs were transfected individually using oligofectamine into B95a cell line. This resulted in SLAM suppression from 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…When the SLAM-suppressed B95a cells was infected with PPRV, replication was reduced by 12-143-fold and virus titre was reduced from log 10 1.09-2.28. This study confirmed that SLAM is one of the (co) receptors for PPRV [27]. However, the presence of other putative virus receptor(s) is/are not ruled out.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…When the SLAM-suppressed B95a cells was infected with PPRV, replication was reduced by 12-143-fold and virus titre was reduced from log 10 1.09-2.28. This study confirmed that SLAM is one of the (co) receptors for PPRV [27]. However, the presence of other putative virus receptor(s) is/are not ruled out.…”
Section: Resultssupporting
confidence: 67%
“…This study also revealed identical aa at positions 60 (Isoleucine) and 61 (Histidine) in caprine SLAM protein, indicating that these residues may have a critical role in the receptor function of SLAM for PPRV. Recently, the effect of SLAM inhibition on PPRV replication and infectivity titre in B95a cell line was studied by Pawar et al [27] using siRNA approaches. When the SLAM-suppressed B95a cells was infected with PPRV, replication was reduced by 12-143-fold and virus titre was reduced from log 10 1.09-2.28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment of an in vitro system using Sungri96 virus shown that RNP complex is actively synthesis mRNA (Yunus and Shaila, 2012). PPRV multiplication was reduced significantly in Signaling Lymphocyte Activation Molecule (SLAM;CD150) receptors suppressed with siR-NA in B95a (Pawar et al, 2008b).Transiently expressed PPRV F glycoprotein induces cell fusion in the absence of H protein (Seth and Shaila, 2001). The H protein was found to have potential T cell determinant(s) at amino acids position 123-137 and 242-609 (Sinnathamby et al, 2001).…”
Section: The Virusmentioning
confidence: 99%
“…Canine SLAM has 65% amino acid identity to human SLAM, while bovine SLAM has 65 and 69% amino acid identity to human and canine SLAM, respectively (Pawar et al 2008a). Pawar et al (2008b) found that SLAM was a cellular receptor for PPRV. This fact suggests that SLAM might be a receptor for several morbilliviruses.…”
Section: Introductionmentioning
confidence: 99%